Interfacial chemistry and morphology of blends of polybutyleneterephthalate and epoxide-containing rubber - Van Duin, Martin (2003)
Of the various ways in which polybutyleneterephthalate (PET) can be toughened, the addition of epoxide-containing rubbers is one of the most effective. The interfacial chemistry (dissolution and fractionation experiments) and morphology (transmission electron microscopy) development in blends of PBT with ethylene-(methyl acrylate)-(glycidyl methacrylate) rubber (E-MA-GMA) has been studied as a function of the mixing time for batch kneaders and of the length along the axis of a co-rotating twin-screw extruder. First, a physics-controlled mixing regime occurs with a very fast dispersion of the rubber to the μm level. Subsequently, a chemistry-controlled regime occurs, where the interfacial area is covered with PBT/E-MA-GMA graft copolymer, which prevents coalescence and, thus, results in further refinement of the morphology to sub-μm level. The occurrence of cross-linking of the rubber phase in some cases limits optimum blend dispersion.